Monitoring Mechanism of Enterprise Industrial Marketing Management - Tetiana KHARCHENKO; Olena KLIBANSKA; Tetіana CHUNIKHINA; Liliia PRYIMAK (Communications of International Proceedings, 2020)
The expediency of taking into account the dynamics of financial state of an enterprise and a competitive strategy at the present stage of strategic price management is substantiated. A matrix of situational price management at an industrial enterprise is developed, in which the choice of strategic guidelines is based on two approaches: the first is based on the needs of customers, the second is based on the technological capabilities of the enterprise itself. The matrix allows to identify a situation where it is appropriate to apply a particular approach. The article focuses on the importance of the monitoring function of industrial marketing management, which provides a specially organized systematic observation of the compliance of the results of industrial marketing management with the defined goals in order to make the necessary corrective management decisions in the modern competitive conditions of enterprises functioning and deepening crisis situations in the external environment.
Keywords: Monitoring; Industrial Marketing; Management Mechanism; Management Decisions; Strategic Management.